PRODUCTION OF WHITE SHRIMP Litopenaeus vannamei IN FLOATING CAGE SYSTEM WITH DIFFERENT STOCKING DENSITY AT THOUSAND ISLAND STRAIT - Sophia N.M. Fendjalang; Tatag Budiardi; Eddy Supriyono; Irzal Effendi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
The aim of this study was to analyze the survival rate, growth, and haemolymp glucose level of white shrimp as a physiological responses at floating cage cultured on different stock den-sity, in Seribu Islands Strait. White shrimp used in this study contained approximate weight of 1.0±0.06 g and length of 5.0±0.03 cm from Nusa Karamba Hatchery in Seribu Island. White shrimp was maintained in 90 days, feed with ±36.28 % protein content 4 times each day with feeding rate (FR) of 7%. Water qualities and shrimp growth measurements was conducted every 10 days. Haemolymph glucose sam-pling was performed in the beginning and at the end of the experiment. Result showed that treatment with stock densituy of 250 shrimp/m2 had a better survival rate of 30.33% and feed conversion ratio of 1.13 than other treatments. Phy-siological response in the form of glucose hemolim also showed a better response in the 250 ind./m2 stock density of 41.87 mg/dl indicating that the white shrimp did not experience a sig-nificant stress. Keywords: Litopenaeus vannamei, sea floating cages, stock density, strait waters, Seribu Islands.